Boosting nutritional quality of Urtica dioica L. to resist climate change - Opačić, Nevena; Radman, Sanja; Dujmović, Mia; Fabek Uher, Sanja; Benko, Božidar; Toth, Nina; Petek, Marko; Čoga, Lepomir; Voća, Sandra; Šic Žlabur, Jana (Frontiers in Plant Science, 2024)
Introduction More than ever, traditional agricultural practices need a shift towards more resilient, sustainable, modern and adaptable practices that benefit the health of the planet and people. Today's consumers are constantly on the lookout for novel, highly nutritious foods that have a positive impact on their overall health and well-being. Nettle (Urtica dioica L.) is gaining recognition not only as a popular medicinal plant, but also as a desirable green leafy vegetable rich in phytonutrients. As it is difficult and even expensive to control the quality standards of wild-collected plants, the implementation of sustainable cultivation methods, especially hydroponics, with effective greenhouse management could be a possible solution to obtain a standardized product with high nutritional value. Therefore, the aim of this study was to investigate the effects of four nutrient solutions differing in the content of macro- and micronutrients (especially nitrogen, potassium, calcium, magnesium and iron) and two consecutive cuts on the number of leaves, yield, nitrate and mineral content and the content of specialized metabolites of stinging nettle from a floating hydroponic system. Methods Nettle plants were cultivated in a hydroponic system using the floating hydroponics technique. The two-factorial experiment was performed with nutrient solution and consecutive cuts as factors. Results The highest yield (2.49 kg/m2) was achieved after the 1st cut with plants cultivated in the nutrient solution with higher nutrient concentration. All tested nutrient solutions resulted in high levels of minerals and bioactive compounds in the plant material (ascorbic acid content of 102.30 mg/100 g fw and total phenolics content of 465.92 mg GAE/100 g fw), confirming floating hydroponics as a sustainable approach for cultivating nettle with enhanced nutritional value and antioxidant potential. Conclusion It is important to highlight that the nutrient solution with the lowest nutrient composition yielded the highest concentrations of calcium (5.54%) and iron (180.67 mg/kg dw). Furthermore, it exhibited elevated levels of specific phenolic compounds, including caffeoylmaleic acid, ellagic acid, ferulic acid, naringin, and rutin trihydrate. Notably, this solution demonstrated the lowest nitrate content (4225.33 mg/kg fw) in the plant material. Therefore, it can be recommended as a preferable formulation for hydroponic nettle cultivation.